Folic acid - influence on male fertility, spermatogenesis, sperm DNA fragmentation and subsequent growth of the embryo and fetus - Truchta, Monika; Augustynowicz, Kinga; Marcinkowska, Marta; Stoliński, Michał; Świąder, Kinga (Journal of Education, Health and Sport, 2023)
Introduction: Men’s infertility is a multifactorial disorder. According to scientific literature, among men with reduced fertility, growing interest in folic acid is observed. This review describes the effect of folic acid on spermatogenesis, sperm concentration, sperm DNA fragmentation and the growth of the embryo and fetus. Material and methods: The work was based on the articles published in PubMed, medical books and websites. Results: Folic acid affects the trajectory of embryo growth in pregnancy conceived spontaneously, there is a negative correlation between the concentration of folic acid in the semen and the indicator of sperm DNA fragmentation and sperm concentration are statistically higher in folic acid supplements. Conclusions: The results suggest that the father’s exposure to folic acid before conception may affect the health of his offspring, and therefore care before conception should be changed from an approach focused on a woman to a couple-based approach.